Current perspectives of lncRNAs in abiotic and biotic stress tolerance in plants - Jin, Xin; Wang, Zemin; Li, Xuan; Ai, Qianyi; Wong, Darren Chern Jan; Zhang, Feiyan; Yang, Jiangwei; Zhang, Ning; Si, Huaijun (Frontiers in Plant Science, 2024)
Abiotic/biotic stresses pose a major threat to agriculture and food security by impacting plant growth, productivity and quality. The discovery of extensive transcription of large RNA transcripts that do not code for proteins, termed long non-coding RNAs (lncRNAs) with sizes larger than 200 nucleotides in length, provides an important new perspective on the centrality of RNA in gene regulation. In plants, lncRNAs are widespread and fulfill multiple biological functions in stress response. In this paper, the research advances on the biological function of lncRNA in plant stress response were summarized, like as Natural Antisense Transcripts (NATs), Competing Endogenous RNAs (ceRNAs) and Chromatin Modification etc. And in plants, lncRNAs act as a key regulatory hub of several phytohormone pathways, integrating abscisic acid (ABA), jasmonate (JA), salicylic acid (SA) and redox signaling in response to many abiotic/biotic stresses. Moreover, conserved sequence motifs and structural motifs enriched within stress-responsive lncRNAs may also be responsible for the stress-responsive functions of lncRNAs, it will provide a new focus and strategy for lncRNA research. Taken together, we highlight the unique role of lncRNAs in integrating plant response to adverse environmental conditions with different aspects of plant growth and development. We envisage that an improved understanding of the mechanisms by which lncRNAs regulate plant stress response may further promote the development of unconventional approaches for breeding stress-resistant crops.